Post liposuction infections by rapidly growing mycobacteria - Zosso, Caroline; Lienhard, Reto; Siegrist, Hans H.; Malinverni, Raffaele; Clerc, Olivier (Infectious diseases (London, England), 2015)
Abstract Rapidly growing mycobacteria (RGM) are recognized agents of surgical site infections. Recently, RGM skin and soft tissue infections have been increasingly reported. As symptoms, clinical signs and disease latency remain non-specific and microbiological detection requires targeted growth media, RGM diagnosis remains challenging for clinicians. Appropriate management is often delayed due to lack of awareness of these infections. RGM infections after plastic surgery have also been described in the setting of interventions performed in developing countries, a growing phenomenon commonly known as medical tourism. We describe a case of Mycobacterium chelonae/abscessus infection following liposuction and liposculpture procedures performed in the Dominican Republic and review the literature on this subject.